The Influence of Tax Burden, Bonus Mechanism, and Debt Covenant on Transfer Pricing Decisions in Manufacturing Companies Listed on the Indonesia Stock Exchange - Fika Ramdhany; Nadila Andriana (Journal of Applied Management and Business Administration, 2022)
This study aims to find out whether the tax burden, bonus mechanism, and debt covenant affect the transfer pricing decision. The factors tested in this study are tax burden, bonus mechanism, and debt covenent, as an independent variable, and transfer pricing as the dependent variable. The research method used was explanatory research. The type of research data in the form of secondary data is the financial statements of manufacturing companies listed on the Stock Exchange during 2013-2017. The population in this study were 155 manufacturing companies listed on the Indonesia Stock Exchange during 2013-2017, with a sample determination technique using purposive sampling technique to obtain 41 companies with 205 annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange during 2013-2017. The results of partial hypothesis testing show that tax burden affects transfer pricing decisions, bonus mechanisms affect transfer pricing, and debt covenent influences transfer pricing. The results of simultaneous hypothesis testing show that the tax burden, bonus mechanism, and debt covenant together influence the transfer pricing. The contribution of tax burden, debt covenent, and company size is influenced by transfer pricing of 72.93%, while the remaining 27.07% is explained by other variables outside the research model.